Multi-Axis Force/Torque Sensor Based on Simply-Supported Beam and Optoelectronics - Yohan Noh; Joao Bimbo; Sina Sareh; Helge Wurdemann; Jan Fraś; Damith Suresh Chathuranga; Hongbin Liu; James Housden; Kaspar Althoefer; Kawal Rhode (Sensors, 2016)
This paper presents a multi-axis force/torque sensor based on simply-supported beam and optoelectronic technology. The sensor’s main advantages are: (1) Low power consumption; (2) low-level noise in comparison with conventional methods of force sensing (e.g., using strain gauges); (3) the ability to be embedded into different mechanical structures; (4) miniaturisation; (5) simple manufacture and customisation to fit a wide-range of robot systems; and (6) low-cost fabrication and assembly of sensor structure. For these reasons, the proposed multi-axis force/torque sensor can be used in a wide range of application areas including medical robotics, manufacturing, and areas involving human–robot interaction. This paper shows the application of our concept of a force/torque sensor to flexible continuum manipulators: A cylindrical MIS (Minimally Invasive Surgery) robot, and includes its design, fabrication, and evaluation tests.